Cellulose Isolation and Characterization of Green Seaweed C. Lentillifera from Halmahera, Indonesia - Mentari, Puji Rizana Ayu; Andreansyah, Ilham; Amanda, Putri; Marlina, Resti; Suharti, Suharti; Agustina, Siti; Syamani, Firda Aulya (Universitas Negeri Semarang, 2023)
Caulerpa lentillifera or known as sea grapes is a type of green seaweed which is rich of nutritional components and widespread in the tropical regions in Asia, including Indonesia. Moreover, C. lentillifera contains of polysaccharides, such as cellulose which has the potential to various applications. In this study, C. lentillifera collected from Halmahera, Indonesia was determined for its chemical compositions (moisture, ash, extractives, hemicellulose, α-cellulose contents) and was extracted to obtain cellulose. Isolation of cellulose from C. lentillifera was done by soxhlet extracted using ethanol-benzene solvent to remove extractives, boiling to increase the amount of cellulose extracted, H2O2 bleaching to eliminate any remaining pigments and other contaminants, and freeze drying to get coarse powder of cellulose. The moisture content, ash, extractives, hemicellulose, α-cellulose of C. lentillifera were 11.94%, 31.62%, 11.53%, 35.57%, and 7.95%, respectively. The yield of cellulose obtained was 31.13% based on seaweed dry weight. FE-SEM (Field Emission-Scanning Electron Microscopy) analysis of C. lentillifera showed colonies of diatoms in elliptical shapes. FTIR (Fourier Transform Infrared) measurements indicating cellulose purity after extraction process. X-Ray Diffraction (XRD) analysis resulted some peaks of salt crystals in C. lentillifera and cellulose of C. lentillifera in amorphous form. After extraction, the crystallinity index of cellulose obtained was 37.3%.